1994
DOI: 10.1007/bf02639394
|View full text |Cite
|
Sign up to set email alerts
|

A continuous culture of pluripotent fetal hepatocytes derived from the 8-day epiblast of the pig

Abstract: SUMMARYContinuous cultures of pluripotent parenchymal hepatocytes were derived from the epiblasts of 8-day-old pig blastocysts. The cells were polygonal and had phase-contrast dark, granular cytoplasm with prominent nuclei and nucleoli.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
25
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 39 publications
4
25
0
Order By: Relevance
“…The differentiation of the pig BDE cells was dramatic in the STO coculture, and it was very similar to the multicellular ductal formation previously observed in the pig epiblast-derived PICM-19 liver stem cell line (Talbot et al, 1994a;. The pig BDE ductal structures were similar to normal liver in that they possessed cilia, a feature typical of pig intrahepatic bile ductules (Singh and Shahidi, 1987).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The differentiation of the pig BDE cells was dramatic in the STO coculture, and it was very similar to the multicellular ductal formation previously observed in the pig epiblast-derived PICM-19 liver stem cell line (Talbot et al, 1994a;. The pig BDE ductal structures were similar to normal liver in that they possessed cilia, a feature typical of pig intrahepatic bile ductules (Singh and Shahidi, 1987).…”
Section: Discussionsupporting
confidence: 77%
“…We have previously demonstrated that STO feeder cells will support the differentiation and growth of pig epiblast-derived, liver stem cell-like cells (Talbot et al, 1994a. We have also shown that STO feeder cells will support the growth of pig fetal liver cells that differentiated into hepatocytes and ductal structures (Talbot et al, 1994b).…”
Section: Introductionmentioning
confidence: 92%
“…That is, it is possible that the PFL low-density ductal structures resulted because there were a finite number of cells committed to ductal formation in the population. In contrast, PICM-19 appeared to replenish its stem cell compartment over passage, and, therefore, retained its ability to differentiate into ductal structures with relatively high cell density (manuscript submitted, Talbot et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Unconcentrated, serumfree conditioned media samples or diluted pig serum (1:50) were prepared as previously described (Talbot et al, 1994). Samples were loaded onto a 10% polyacrylamide gel, and electrophoresis was performed under described conditions (Laemmli, 1970) Hybridizations with a human glyceraldehyde-3-phosphate dehydrogenase DNA probe (pSP6-G3PDH, Ambion, Austin, TX) or a rabbit a-actin DNA probe, provided by Dr. Roger T. Stone, were subsequently performed as loading controls.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation